Association between vaccination and myasthenia gravis: a systematic review and meta-analysis - Guan, Chang; Zhang, Ruonan; Zhao, Peixi; Zhang, Ying; Yu, Lan; Cui, Huijing; Jiang, Li; Wu, Tong; Liu, Fang; Wu, Yang; Huang, Lin; Nan, Hongmei; et al. (Frontiers in Immunology, 2026)
BackgroundMyasthenia gravis (MG) is a rare autoimmune disorder characterized by fluctuating muscle weakness due to impaired neuromuscular transmission. Vaccination remains a cornerstone of infectious disease prevention, yet concerns persist regarding potential autoimmune exacerbation in susceptible individuals. This systematic review and meta-analysis aimed to synthesize available evidence on the association between vaccination and MG, evaluating both vaccine effectiveness and safety in this population.MethodsObservational studies in cohort or case-control formats were identified through systematic searches of PubMed, Web of Science, Embase, Cochrane Library, SinoMed, CNKI, Wanfang, and VIP databases from inception to June 24, 2025. Study quality was assessed using the Newcastle–Ottawa Scale (NOS). Pooled odds ratios (OR) with 95% confidence intervals (CI) were calculated using fixed- or random-effects models based on heterogeneity. Publication bias was assessed using funnel plots and Egger’s test.ResultsFive studies encompassing 27,193 participants (22,618 vaccinated and 4,575 unvaccinated) met inclusion criteria. Meta-analysis demonstrated a significant protective effect of vaccination against COVID-19 infection (fixed-effects model: OR = 0.23, 95% CI [0.20–0.26], P < 0.001). Conversely, vaccination was not associated with a statistically significant increase in MG exacerbation (random-effects model: OR = 0.67, 95% CI [0.10–4.54], P = 0.68).ConclusionsThis study provides quantitative evidence that COVID-19 vaccination effectively reduces infection risk without significantly increasing MG exacerbation. These findings support the safety and clinical utility of vaccination in MG patients, emphasizing the need for individualized risk–benefit assessment and ongoing pharmacovigilance in this population.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD420251078995.